A review on polymer-based materials for underwater sound absorption. (April 2021) - Fu, Yifeng; Kabir, Imrana I.; Yeoh, Guan Heng; Peng, Zhongxiao
Abstract: Greater demands for underwater sound absorption materials have been growing due to the concern about underwater noise control in water. Among the range of existing materials, polymer-based materials are increasingly being utilized as underwater sound absorption materials. In this paper, different kinds of polymer-based materials for underwater sound absorption with regards to key factors associated with sound absorption properties, measurements, applications, and mechanisms are reviewed and summarized. Commonly used polymers for underwater sound comprise, in general, interpenetrating polymer networks (IPN), polymer foams, and gradient polymers. To further improve underwater sound absorption performance, different types of inclusions that are introduced into the polymer matrix to transform the polymers as underwater sound absorption materials via air voids, solid inclusions, nanofillers, and phononic crystals are discussed. Challenges for further development of better polymer-based acoustic materials to meet requirements of current and future underwater applications are also presented. Highlights: Key factors and tests of polymer-based underwater sound absorption materials. Different polymers with or without inclusions for underwater sound absorption. Mechanisms behind the underwater sound absorption. Challenges for further improving polymer-based underwater water sound absorption materials.